Cara, vecchia metonimia: un ritorno inatteso (ENTHYMEMA, 2020)
The countless changes in rhetorical studies have brought the classic “art of discourse” to a systematic breakdown: first, only in favor of elocutio, then, of poetic lexis and finally, of metaphor. The innumerable changes in rhetoric have led the classic “art of speaking” to a systematic breakdown, first in favor only of elocutio, then of poetic lexis, finally of metaphor. The metonymy was most affected by the new structure of “tropological reduction”. After a moment of success, starting from the last two decades of the twentieth century, the metonymy was mistreated and downgraded to a second-rate trope compared to the metaphor. In the last fifteen years, thanks to cognitive sciences and neurosciences, the scientific community has started to recognize metonymy as a primary role in the cognitive ecosystem. The metonymy has even been recognized as superior at a bio-evolutionary and neuro-physiological level, compared to the metaphor, considered a secondary phenomenon and more disconnected from the experiential spheres of the daily habitat. The functioning of the brain is programmed to use metonymies thanks to both the ability of inferential reasoning and the fact that emotions and physiological symptoms are linked in an incessant metonymic operation. In particular, this occurs when conditioned stimuli predict and subsume unconditioned emotions. In this way impulse self-control is encouraged.
Keywords: restricted rhetoric; metonymy; metaphor; emotions; inferential reasoning; neuro-rhetoric.